Simplify the following question given above
![Simplify the following question given above class=](https://us-static.z-dn.net/files/d32/82133da98d2dc29a827853ab7d6fee3e.png)
Answer:
a) 5⁵ = 3125
Step-by-step explanation:
Explanation:-
Given
[tex]\frac{3^{-5} X 10^{-5} X 125 }{5^{-7} X 6 ^{-5} }[/tex]
on simplification , we get
= [tex]\frac{3^{-5} X (5 X 2)^{-5} X(5)^{3} }{5^{-7} X (3 X 2) ^{-5} }[/tex]
By using algebraic formula
(ab)ⁿ = aⁿ b ⁿ
= [tex]\frac{3^{-5} X (5)^{-5} X (2)^{-5} X(5)^{3} }{5^{-7} X{(3^{-5} } )(2) ^{-5} }[/tex]
after cancellation , we get
= [tex]\frac{ (5)^{-5} X(5)^{3} }{5^{-7} }[/tex]
= [tex](5)^{-5} X(5)^{3} X (5)^{7}[/tex]
= 5⁻⁵⁺³⁺⁷
= 5⁵
= 3125
final answer:-
[tex]\frac{3^{-5} X 10^{-5} X 125 }{5^{-7} X 6 ^{-5} } = 3125[/tex]